Reconciling Two Views of Cryptography (The Computational Soundness of Formal Encryption) - Abadi, Martin; Rogaway, Phillip (Journal of Cryptology, 2002)
Erratum: The online contents page of the original article (DOI: 10.1007/s00145-001-0014-7) was inadvertently published with only the first author appearing. The correct version appears above. The publisher regrets and apologizes for the error.